Analysis of the sensitivity of structural framing and building envelope specifications of a residential building to design wind speed - Morillo, Luis Ariel B.; Aquino, Diocel Harold M.; Pacheco, Benito M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Modifying the design wind speed in the structural code of the Philippines brings about changes in the design of structures to be built. An increase in design wind speed entails changes in a structural frame and building envelope of an existing structure just so it can keep up with the required specifications for a design wind speed. This paper studies the correlation between the design wind speed and specifications for the structural frame and building envelope. This is done through the analysis of a residential building ,representative of the typical design found in the Philippines, using a structural analysis and design software. The structure would be designed to withstand the wind loading subjected to it prescribed in the NSCP for the corresponding design wind speed. This process starts from a design wind speed of 1OOkph increases up to 325kph with an increment of25kph to form a graph relating the design wind speed and specification for a structural member or a component of the building envelope. The results show that the reinforced concrete beams of the structure are sensitive to change when design wind speed is increased from 175kph, 250kph, and 300kph. The reinforced concrete columns, in the other hand, changed specification when design wind speed exceeded 275kph. As for the steel rafter, this component of the structural frame changed specifications only when design wind speed increased from 300kph prompting the steel rafter to increase by upgrading the size of the channel to the next heavier steel channel section provided in ASTM. For the structure's building envelope, the quantity of the teck screw is shown to be sensitive to change in every increase in design wind speed. The quantity of the teck screw increased until it nearly fills the capacity of the purl in to hold anymore in roof areas subjected to the highest wind pressure. As for the purl in spacing, it reacts considerably to wind forces at design wind speeds higher than 225kph.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Wind resistant design; Buildings -- Aerodynamics; Wind-pressure.